HUKUM TINGKEBAN PADA ADAT JAWA MENURUT HUKUM ISLAM (STUDI KASUS DESA SUKA DAMAI KECAMATAN SEI BAMBAN KABUPATEN SERDANG BEDAGAI ) - Sufathudin, Sufathudin (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
Tingkeban is a local tradition that is still implemented by Javanese people. The implementation of tingkeban was formed from an old pattern that is before the teachings of Islam entered Indonesia which was still closely related to Hindu culture originating from the kingdom of Kediri. But seen from the development of the implementation of this tradition increasingly shows Islamic values as the implementation of tingkeban in Suka Damai Village, Sei Bamban District, Serdang Bedagai Regency. The Islamic teachings contained in that is salvation or expression of gratitude to Allah SWT as the creator and provider of sustenance and gifts to humans and children is one of the gifts among the many gifts given. Tingkeban is also a traditional tradition of people in Java for generations that can indirectly increase the trust of a mother and father to keep praying so that they are blessed with a blessed and shilihah baby, by drawing closer to Allah SWT. Basically, during pregnancy has a goal that the process of pregnancy until birth can run smoothly without obstacles, and babies born are given safety. The opinion of the MUI leader, Mr. Zainuddin, as the MUI chairman of the Sei Bamban sub-district, believes that tingkeban is a salvation when the baby in the womb is seven months old, aiming that the child born will be healthy, safe, no defects and not lacking one, so we recommend to pray, and give thanks for the blessings that have been given by Allah SWT. And pregnancy is a favor or gift that Allah SWT gives to a husband and wife to get offspring. Therefore, in addition to praying we also give alms and alms as an expression of gratitude.